Insulin mimicking activities of Cycloartane Triterpenoid in 3T3-L1 cells - Bakhtiar, M. Taher; Mohamed Amiroudine, Mohamed Zaffar Ali; Darnis, Deny Susanti; Ichwan, Solachuddin J. A.; Kaderi, Mohd Arifin (2013)
Type 2 diabetes is a metabolic disorder characterized by insulin resistance, insulin action and caused by multifactorial etiology, including environmental factors, particularly diet and genetic components. Recently, most research on diabetes has focus on adipocyte which is used as a model for testing of insulin sensitivity and novel antidiabetic drugs. In this study, we investigated the effects of cycloartane triterpenoid on the adipocyte differentiation and glucose uptake in 3T3-L1 cells together with its underlying gene expression. The cells were treated for triglyceride accumulation with different concentration of the compound using Oil Red O staining assay. After 8-days, morphological changes and increase lipid accumulation were observed in these cells (p<0.05). Indeed, the intracellular lipid accumulation increased by 1.9 fold relative to MDI-treated control cells at concentration of 50 µM. Analysis of insulin-induced 2-deoxy-D-[3H] glucose uptake activities shows that cycloartane triterpenoids significantly (p<0.01) improved the glucose uptake with increasing the concentration of the compounds as compared to the basal. Further evaluation with the quantitative real time polymerase chain reaction (qRT-PCR) shows that mature 3T3-L1 cells treated with cycloart-24-en-3β-ol enhance pparγ and glut4 gene expression. As a result, it demonstrated that cycloartane triterpenoids enhance pparγ and glut4 gene expression. Taken together, these results suggest that cycloart-24-en-3β-ol derived from Garcinia malaccencis could improve insulin sensitivity through the activation of pparγ as a ligand and glut4.